Tigridia rzedowskiana (Tigridieae: Iridaceae), a new species from the state of Queretaro, Mexico - Rodríguez, Aarón; Ortiz-Catedral, Luis (Instituto de Ecología, A.C., 2005)
Tigridia rzedowskiana (Tigridieae: Iridaceae) is a new species found in the state of Querétaro, Mexico. It is unique by its yellowish flowers with maroon spots, outer tepals obovate, obtuse to apiculate and inner tepals deltate-hastate and apiculate. The flowers open early in the morning. Tigridia rzedowskiana is morphologically similar to T. catarinensis and we discuss their differences.